2018
DOI: 10.1177/0956797617744542
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Crime: Integrating New Genomic Discoveries Into Psychological Research About Antisocial Behavior

Abstract: Drawing on psychological and sociological theories of crime causation, we tested the hypothesis that genetic risk for low educational attainment (assessed via a genome-wide polygenic score) is associated with criminal offending. We further tested hypotheses of how polygenic risk relates to the development of antisocial behavior from childhood through adulthood. Across the Dunedin and Environmental Risk (E-Risk) birth cohorts of individuals growing up 20 years and 20,000 kilometers apart, education polygenic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 40 publications
8
57
1
1
Order By: Relevance
“…No sex differences were observed regarding the relationship between the EA PGS and higher education status and achievement. This is consistent with work that has found that participant sex did not influence the relationship between polygenic propensity for education attainment and higher education in samples of predominantly European heritage . However, we found that a higher EA PGS was negatively associated with criminal offending among males, but not females, conflicting with findings reported by Wertz et al who found no sex differences in polygenic propensity for educational attainment and criminal offending.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…No sex differences were observed regarding the relationship between the EA PGS and higher education status and achievement. This is consistent with work that has found that participant sex did not influence the relationship between polygenic propensity for education attainment and higher education in samples of predominantly European heritage . However, we found that a higher EA PGS was negatively associated with criminal offending among males, but not females, conflicting with findings reported by Wertz et al who found no sex differences in polygenic propensity for educational attainment and criminal offending.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with work that has found that participant sex did not influence the relationship between polygenic propensity for education attainment and higher education in samples of predominantly European heritage . However, we found that a higher EA PGS was negatively associated with criminal offending among males, but not females, conflicting with findings reported by Wertz et al who found no sex differences in polygenic propensity for educational attainment and criminal offending. The sex differences observed may be largely driven by differences in incarceration rates among males and females, socialization, expectations for males and females, and the effect of contextual factors (eg, peers) among males compared with females .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations